2012
DOI: 10.2478/v10236-012-0006-1
|View full text |Cite
|
Sign up to set email alerts
|

The Concentration of Immunoglobulins A, G, and M in Cow Milk and Blood in Relation with Cow Seasonal Keeping and Pathogens Presence in the Udder

Abstract: The Concentration of Immunoglobulins A, G, and M in Cow Milk and Blood in Relation with Cow Seasonal Keeping and Pathogens Presence in the UdderRecent studies show that immunoglobulins A, G, and M contribute significantly to the maintenance of udder health. Unfortunately, the concentration of immunoglobulins in cow milk during the middle period of lactation is low therefore the question of how to stimulate and maintain a sufficient level and spectrum of antibodies in the udder is topical. The aim of the presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 17 publications
2
11
0
2
Order By: Relevance
“…The present research data are in agreement with the results of Hagiwara et al (2003) where LF concentration in quarters of cows infected with S.aureus and with other streptococci species were higher in comparison to CNS (coagulase negative staphylococcus). Investigations by Chaneton et al (2008) and Kocina et al (2012) showed that LF and IgG concentrations are induced by different bacteria, with Streptococcus uberis causing the highest increase. Kocina et al (2012) indicated that in the case of S.aureus infection the IgG mean value was lower even than in healthy quarter milk.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The present research data are in agreement with the results of Hagiwara et al (2003) where LF concentration in quarters of cows infected with S.aureus and with other streptococci species were higher in comparison to CNS (coagulase negative staphylococcus). Investigations by Chaneton et al (2008) and Kocina et al (2012) showed that LF and IgG concentrations are induced by different bacteria, with Streptococcus uberis causing the highest increase. Kocina et al (2012) indicated that in the case of S.aureus infection the IgG mean value was lower even than in healthy quarter milk.…”
Section: Discussionmentioning
confidence: 99%
“…Investigations by Chaneton et al (2008) and Kocina et al (2012) showed that LF and IgG concentrations are induced by different bacteria, with Streptococcus uberis causing the highest increase. Kocina et al (2012) indicated that in the case of S.aureus infection the IgG mean value was lower even than in healthy quarter milk.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Segundo dados do IBGE (2014), em 2013 a população de búfalos no país era de 1,33 milhão de animais, sendo que a região Sudeste apresentou um aumento de 4,3% do rebanho relativamente a 2012. O maior interesse pela criação de bubalinos deve-se ao fato da búfala produzir leite com características peculiares, com teor de sólidos que supera consideravelmente o do leite de vaca.…”
Section: Introductionunclassified